ANALISIS IQTIBÄ€S DALAM SYAIR IBNU JABIR AL ANDALUSIA - Sarifah, Sarifah (ALSUNIYAT: Jurnal Penelitian Bahasa, Sastra, dan Budaya Arab, 2019)
Al-Qurâ€™an has the beautiful meaning and language style that can reach the soul of the listene From there BalÄgah science appear that the suitability of fluent and proper sentence could be applied to the meaning of appropriate lafaz. In BalÄgah science there are three own discussion namely: ilmu maâ€™Äni, ilmu bayÄn, and ilmu badÄ«â€™. IqtibÄs is one of part ilmu badÄ«â€™, which make many Arabic poets that cite Al-Qurâ€™an, because of the sentences and the selection of lafaz which make the poets fascinated by the beauty of its language style. This research used a descriptive analsis of qualitative research on the poem ofÂ  Ibnu Jabir Al Andalusia.